Possibilidades para um material didático de filosofia na Educação de Jovens e Adultos (EJA) - Fernanda Campos de Miranda (2023)
This work presents the results of the research on the possibilities of building a philosophy didactic material for the subjects of education for teens and adults (EJA). The central issue of this research is to contribute to the philosophical proximity between the knowledge of tradition and the knowledge of everyday life of EJA subjects. In this work, we criticize coloniality and eurocentrism present in the teaching of philosophy in Brazil, based on Decolonial Thought, some theorists of Philosophy of Liberation and studies of Brazilian and Latin American Philosophy. The text is divided into three chapters. In the first chapter, we present the State of the Question; we made a record of how the object of investigation of this research is found in the current state of science. In the second chapter, we present the theoretical basis for the production of didactic material for teaching philosophy in EJA. And, in the third chapter, we present how the elaboration of the didactic material that we have proposed was in practice; we make a brief presentation of the school space, the subjects involved in the research and what they enunciated about the didactic material that was collectively constructed. The constructed work intends to be a contribution for the EJA philosophy teachers; we present material outside the colonial and eurocentric molds. The research aims to encourage educators from the public education network to fight for continuing education, claim that the State takes responsibility for it, not only in documents, but in practice, offering remuneration, time and space for it to happen. Finally, this work intends to present the struggle and challenges faced in a public school, on the outskirts of Belo Horizonte, in the Philosophy discipline, in the EJA teaching modality.